Surgical management of delayed-presentation diaphragm hernia: A single-institution experienceCentral MessagePerspective - Emma K. Jones, MD; Rafael Andrade, MD, MHA; Amit Bhargava, MD; Ilitch Diaz-Gutierrez, MD; Madhuri Rao, MD, FACS (JTCVS Techniques)
Objectives: Delayed-presentation diaphragm hernias are uncommon, and surgical management varies widely across practices. We describe our surgical experience with delayed-presentation diaphragm hernias as a case series of 14 patients, 9 of whom underwent minimally invasive repair. Methods: We performed a retrospective chart review of our prospective database of all patients treated surgically for delayed-presentation diaphragm hernia at our institution from January 1, 2005, to April 30, 2021. We excluded patients with poststernotomy, post–left ventricular assist device, and previously diagnosed congenital hernias. We recorded patient demographics, etiology, laterality, chronicity, operative details, postoperative complications, and long-term results. Results: We performed surgical repair of delayed-presentation diaphragm hernia in 14 patients. Eleven patients (79%) were male, the median age was 61 (18-83) years, the median body mass index was 29.2 (14.5-33.7), and 8 (57%) hernias were left-sided. Etiology was trauma (n = 7, 50%), iatrogenic (n = 5, 36%), and unknown (n = 2, 14%). Median time to presentation in patients with traumatic and iatrogenic hernias was 7.5 years (6 weeks to 38 years). Nine patients (64%) underwent minimally invasive repair, and 5 patients (36%) underwent open repair. We used a synthetic patch in all but 2 patients (86%). Median length of stay was 5 (3-27) days. Two patients (14%) had major complications. There were no deaths. Twelve patients (86%) had follow-up imaging at a median follow-up of 17 months (1-192) with zero recurrences. Conclusions: Our experience suggests that a minimally invasive or an open approach to patients with a delayed-presentation diaphragm hernia is safe and effective. We recommend tailoring the surgical approach based on patient characteristics, anatomic considerations, and surgeons’ experience.